Fragmentation patterns of evergreen oak woodlands in Southwestern Iberia: Identifying key spatial indicators - Costa, Augusta; Madeira, Manuel; Lima Santos, José; Plieninger, Tobias; Seixas, Júlia (Journal of Environmental Management, 2014)
Abstract Mediterranean evergreen oak woodlands (composed of Quercus suber L. and Quercus rotundifolia Lam.) are becoming increasingly fragmented in the human-modified landscapes of Southwestern Portugal and Spain. Previous studies have largely neglected to assess the spatial changes of oak woodlands in relation to their surrounding landscape matrix, and to characterize and quantify woodland boundaries and edges. The present study aims to fill this gap by analyzing fragmentation patterns of oak woodlands over a 50-year period (1958–2007) in three landscapes. Using archived aerial imagery from 1958, 1995 and 2007, for two consecutive periods (1958–1995 and 1995–2007), we calculated a set of landscape metrics to compare woodland fragmentation over time. Our results indicated a continuous woodland fragmentation characterized by their edge dynamics. From 1958 to 2007, the replacement of open farmland by shrubland and by new afforestation areas in the oak woodland landscape surrounding matrix, led to the highest values for edge contrast length trends of 5.0 and 12.3, respectively. Linear discriminant analysis was performed to delineate fragmented woodland structures and identify metric variables that characterize woodland spatial configuration. The edge contrast length with open farmland showed a strong correlation with F1 (correlations ranging between 0.55 and 0.98) and may be used as a proxy for oak woodland mixedness in landscape matrix. The edge dynamics of oak woodlands may result in different patterns of oak recruitment and therefore, its study may be helpful in highlighting future baselines for the sustainable management of oak woodlands.
Keywords: Forest change; Forest spatial pattern; mediterranean forest; Oak woodlands; Quercus rotundifolia; Quercus suber

The role of holm oak edges in the control of disturbance and conservation of plant diversity in fire-prone landscapes - Azevedo, J.C. C C; Possacos, a.; Aguiar, C.F. F F; Amado, a.; Miguel, L.; Dias, R.; Loureiro, C.; Fernandes, P.M. M M (Forest Ecology and Management, 2013)
Holm oak (Quercus rotundifolia) woodlands have been able to persist in ﬁre-prone landscapes in northern Portugal where they seem to play a relevant role in community and landscape level patterns and processes, namely in the control of disturbance events and in the maintenance of biodiversity. In this research we tested the following hypotheses: (i) holm oak woodlands affect ﬁre behavior, mainly by disrupting and delaying ﬁre spread; (ii) disruption and delaying of ﬁre spread is due to ﬁre extinction at the edge of woodlands; and (iii) plant diversity is favored by frequent low-intensity ﬁres as a result of the control of ﬁre spread by holm oak woodland edges. We sampled herbaceous, shrub and tree structure and herbaceous plant composition across edges of holm oak woodlands with known recent contact with ﬁre. Using BehavePlus we converted structural data into fuel models and simulated ﬁre behavior for the locations sampled along the exterior–interior gradient of the woodlands. Our results indicate that holm oak woodlands play a relevant role in the control of ﬁre spread and in the maintenance of plant diversity. We found differences in simulated maximum rate of ﬁre spread (ROS) and ﬁreline intensity (FLI) between outside and inside woodlands as well as a 100% probability of ﬁre extinction when fuel moisture was >12% and wind speed at 10 m aboveground was <40 km h1 , supporting the self-extinction hypothesis. We found also that richness and abundance of herbaceous plants varied between the interior and exterior of the woodland, with higher values outside the woodland, and that plant composition along the interior– exterior gradient had distinct patterns. These variables and the pattern of plant distribution were also signiﬁcantly affected by time since last ﬁre event. We conclude that holm oak woodlands affect ﬁre behavior by interrupting ﬁre spread at the edge zone and that ﬁre-created edges affect herbaceous plant species richness, abundance and distribution by maintaining habitat diversity, which increased plant diversity at patch and landscape levels. Based on our results and other evidence, we developed a conceptual model of the dynamics of ﬁre, landscape structure, and plant diversity in ﬁre-prone landscapes where holm oak patches persist.
Keywords: Edges; Fire behavior; Mediterranean Region; plant diversity; Portugal; Quercus rotundifolia

Lupinus luteus, a new host of Phytophthora cinnamomi in Spanish oak-rangeland ecosystems - Serrano, María Socorro; Fernández-Rebollo, Pilar; Vita, Paolo; Carbonero, María Dolores; Trapero, Antonio; Sánchez, María Esperanza (European Journal of Plant Pathology, 2010)
Phytophthora cinnamomi is an aggressive pathogen on Lupinus luteus (yellow lupin), causing root rot, wilting and death of this crop, common in oak-rangeland ecosystems ('dehesas') in south-western Spain. The oomycete, the main cause of Quercus decline in the region, was isolated from roots of wilted lupins in the field. Artificial inoculations on four cultivars of L. luteus reproduced the symptoms of the disease, both in pre- and post-emergence stages, recovering the pathogen from necrotic roots. These results suggest the potential of yellow lupin as inoculum reservoir for the infection of Quercus roots. This is the first report of P. cinnamomi as root pathogen of L. luteus.
Keywords: Oak decline; quercus ilex ssp ballota; Quercus rotundifolia; root rot

Fertilización tardía y establecimiento de Quercus ilex subsp. ballota 2/11 - CORTINA, J.; MONERRIS, J.; DISANTE, K.; FUENTES, D.; VALDECANTOS, A. (V Congreso Forestal Español, 2009)
La restauración de ecosistemas mediterráneos con frecuencia requiere la reintroducción de especies leñosas. Pero existe una gran incertidumbre sobre las características que debe reunir un brinzal para aumentar sus probabilidades de éxito en el campo. Algunos estudios han mostrado que la fertilización en vivero permite una mayor supervivencia y crecimiento en campo. Sin embargo, en estos experimentos, las variaciones en el estado nutricional no se pueden desligar de los cambios morfológicos que promueve la fertilización. Para evaluar la importancia del estado nutricional, frente a las variaciones morfológicas inducidas por éste, hemos evaluado el comportamiento en el campo de brinzales de una savia de Quercus ilex subsp. ballota no fertilizados y brinzales a los que se aplicó fertilización tardía (posterior a la parada otoñal de crecimiento de la parte aérea). Nuestras hipótesis son: (i) la fertilización tardía permite mejorar el estado nutricional de los brinzales sin variar su tamaño y (ii) con ello, se aumenta la supervivencia y el crecimiento de los brinzales en el campo. La fertilización tardía no afectó al tamaño de los brinzales, pero mejoró su estado nutricional. En campo, la supervivencia fue muy elevada antes del primer verano (>98%), disminuyendo después del mismo hasta un rango de valores de 65-100%. En ningún caso la supervivencia estuvo relacionada con la fertilización en vivero. Por el contrario, la tasa de crecimiento antes del verano fue inferior en plantas no fertilizadas, invirtiéndose esta tendencia durante el verano. La tasa anual de crecimiento fue superior en las plantas fertilizadas, confirmando parcialmente nuestra hipótesis. La fertilización tardía representa una técnica sencilla para reducir el uso de fertilizantes en vivero, produciendo brinzales de pequeño tamaño pero elevada capacidad de respuesta en campo. Palabras
The following values have no corresponding Zotero field: periodical: V Congreso Forestal Español pub-location: Avila
Keywords: cultivo en vivero; encinares; estado nutricional; Quercus rotundifolia; restauración forestal

Fertilización tardía y establecimiento de Quercus ilex subsp. ballota 2/11 - CORTINA, J; MONERRIS, J; DISANTE, K; FUENTES, D; Valdecantos, a (V Congreso Forestal Español, 2009)
La restauración de ecosistemas mediterráneos con frecuencia requiere la reintroducción de especies leñosas. Pero existe una gran incertidumbre sobre las características que debe reunir un brinzal para aumentar sus probabilidades de éxito en el campo. Algunos estudios han mostrado que la fertilización en vivero permite una mayor supervivencia y crecimiento en campo. Sin embargo, en estos experimentos, las variaciones en el estado nutricional no se pueden desligar de los cambios morfológicos que promueve la fertilización. Para evaluar la importancia del estado nutricional, frente a las variaciones morfológicas inducidas por éste, hemos evaluado el comportamiento en el campo de brinzales de una savia de Quercus ilex subsp. ballota no fertilizados y brinzales a los que se aplicó fertilización tardía (posterior a la parada otoñal de crecimiento de la parte aérea). Nuestras hipótesis son: (i) la fertilización tardía permite mejorar el estado nutricional de los brinzales sin variar su tamaño y (ii) con ello, se aumenta la supervivencia y el crecimiento de los brinzales en el campo. La fertilización tardía no afectó al tamaño de los brinzales, pero mejoró su estado nutricional. En campo, la supervivencia fue muy elevada antes del primer verano (>98%), disminuyendo después del mismo hasta un rango de valores de 65-100%. En ningún caso la supervivencia estuvo relacionada con la fertilización en vivero. Por el contrario, la tasa de crecimiento antes del verano fue inferior en plantas no fertilizadas, invirtiéndose esta tendencia durante el verano. La tasa anual de crecimiento fue superior en las plantas fertilizadas, confirmando parcialmente nuestra hipótesis. La fertilización tardía representa una técnica sencilla para reducir el uso de fertilizantes en vivero, produciendo brinzales de pequeño tamaño pero elevada capacidad de respuesta en campo. Palabras
Keywords: cultivo en vivero; encinares; estado nutricional; Quercus rotundifolia; restauración forestal

Estimation of tree water stress from stem and soil water monitoring with timeâ€domain reflectometry in two small forested basins in Spain - HERNÁNDEZ-SANTANA, VIRGINIA; MARTÍNEZ-FERNÁNDEZ, JOSÉ; Morán, Carlos (Hydrological P, 2008)
Soil-tree water relationships were studied using time domain reﬂectometry (TDR) in two small forested basins in Spain. The stem water content of two Mediterranean Quercus species (Quercus pyrenaica and Quercus rotundifolia) was measured using previously constructed species-speciﬁc equations. To monitor soil moisture, a TDR station network was used in both cases. Sixteen Q. pyrenaica and six Q. rotundifolia individuals were selected to install two TDR probes in their trunks (at 20 and 120 cm above the ground) to monitor stem water content. Stem and soil water contents were measured fortnightly. The stem water content of both species showed a similar temporal trend for the period studied. A spring maximum (0Ð654 cm3 cm3 for Q. pyrenaica and 0Ð568 cm3 cm3 for Q. rotundifolia) was found to be associated with high transpiration and no soil moisture deﬁcit, and a late-summer minimum (0Ð520 cm3 cm3 for Q. pyrenaica and 0Ð426 cm3 cm3 for Q. rotundifolia) was associated with the end of the dry season. This drop in stem water content occurs when the available water in the soil decreases. This seasonal difference presumably reﬂects water withdrawn from stem storage to support the transpirational demands of the tree. Since plant water stress results in reduced stem water content and since this drop can be measured by TDR, it may be concluded that this technology offers a suitable tool for detecting plant water stress
Keywords: Quercus pyrenaica; Quercus rotundifolia; soil water deficit; stem water content; TDR; water stress

Materia orgánica de suelos bajo encinas. Mineralización de carbono y nitrógeno - Gonzalez Parra, J; Candás Villar, M A (Forest Systems, 2008)
Soil characteristics under evergreen oaks forest (Quercus rotundifolia Lam.) located at the East of Segovia were studied. The soils were formed from gneis and limestone. The whole soil was 0-20 cm depth. The soils were classified as mollic Leptosols, eutric Cambisols and calcaric Cambisols. Horizons sequences were the following: O, Ah1, Ah2, C and O, Ah1, Ah2, BC. Organic horizons (3-0 cm depth) were formed by the not-yet decomposed organic remains from evergreen oaks. Mean organic matter content was 25%. The C:N ratio was high and free organic carbon was near 90% of the total carbon, which correspond with a low degree of humification. Soil texture was loamy sand and sandy loam. Soils on limestone present the highest clay fraction contents. The bases saturation degree was high, being Ca 2+ the fundamental cation of exchange complex. Organic matter content and C:N ratio were lower in organic minerals horizons than in organic horizons. Humification degree was 60% with a predominance of HAs over FAs. The polimerization of humic substances makes possible the formation of humus «moder». Carbon mineralization to the total C was ten times higher than nitrogen mineralization in upper horizons. In all horizons the nitrification was higher than N mineralization. Carbon mineralization was lower and N mineralization was higher in deeper horizons compearing with upper horizons.
Keywords: mineralization; nitrogen; organic matter; Quercus rotundifolia; soils

TDR measurement of stem and soil water content in two Mediterranean oak species - HERNÁNDEZ-SANTANA, VIRGINIA; MARTÍNEZ-FERNÁNDEZ, JOSÉ (Hydrological Sciences Journal, 2008)
Abstract Since 1990s, time domain reflectometry (TDR) has been applied to estimate the stem water content of living trees. Here, new calibration equations relating the apparent dielectric constant (Ka ) to the volumetric water content (?) were developed for two Mediterranean oak species. Our calibration equations differ from those previously calculated for other species, suggesting that stem water contents could be monitored more accurately using species-specific curves. The stem water content in the trees of these species and the surrounding soil were monitored with TDR to examine the feasibility of this technology for recording changes in trunk water storage. The average stem water contents of the oaks reflect the soil water contents, and the temporal differences observed (17%) point to the importance of trunk water for coping with soil water deficit. Although it would be very useful to obtain a single function to estimate the stem water content of trees, it remains necessary to obtain the results in more species.
doi: 10.1623/hysj.53.4.921
Keywords: Quercus pyrenaica; Quercus rotundifolia; Soil moisture; stem water content; TDR

TDR measurement of stem and soil water content in two Mediterranean oak species - HERNÁNDEZ-SANTANA, VIRGINIA; MARTÍNEZ-FERNÁNDEZ, JOSÉ (Hydrological Sciences Journal, 2008)
Abstract Since 1990s, time domain reflectometry (TDR) has been applied to estimate the stem water content of living trees. Here, new calibration equations relating the apparent dielectric constant (Ka ) to the volumetric water content (?) were developed for two Mediterranean oak species. Our calibration equations differ from those previously calculated for other species, suggesting that stem water contents could be monitored more accurately using species-specific curves. The stem water content in the trees of these species and the surrounding soil were monitored with TDR to examine the feasibility of this technology for recording changes in trunk water storage. The average stem water contents of the oaks reflect the soil water contents, and the temporal differences observed (17%) point to the importance of trunk water for coping with soil water deficit. Although it would be very useful to obtain a single function to estimate the stem water content of trees, it remains necessary to obtain the results in more species.
doi: 10.1623/hysj.53.4.921doi: 10.1623/hysj.53.4.921The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Quercus pyrenaica; Quercus rotundifolia; Soil moisture; stem water content; TDR

Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G. (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia

Fire effects on the composition of Pinus halepensis and Quercus rotundifolia communities in the Bou-Taleb Forest, Algeria, with application of a multivariable analysis - Madoui, Amar; Goldammer, Johann G (Forest Ecology and Management, 2006)
The effect of forest ﬁre on the ﬂora of Bou-Taleb’s forest was studied using a Factorial Correspondence Analysis (FCA). This analysis, implemented by using the Braun-Blanquet method, was applied on ﬂoristic releves investigated on Aleppo pine (Pinus halepensis) and on Holm oak (Quercus rotundifolia) communities which burned at different dates. Other ones represent the non-burnt communities and were used as control. Two analyses were used with all releves (160) and all the species which f > 1 (323). The ﬁrst analysis is applied with a presence-absence coefﬁcient and the second one with an abundance-dominance coefﬁcient. The third analysis involved only releves of burned communities (98) and all species (361). The results of all analyses show the time elapsed since ﬁre (ﬂoristic age) is a discrimination factor. We found a clear separation of young communities on the one side, which appeared immediately after ﬁre, and older communities on the other side. Also, ﬁre effects were linked to the type of communities. There is a distinct difference between Aleppo pine and Holm oak communities. There is invasion of therophytes on the parcels recently burned. Few years after ﬁre, the ﬂoristic composition and structure of communities will be the same as on unburned sites.
Keywords: Aleppo pine; Algeria; FCA; Forest ﬁres; Holm oak; Pinus halepensis; Quercus rotundifolia

Chlorophyll degradation effected by lichen substances - Bouaid, K; Vicente, C (ANNALES BOTANICI FENNICI, 1998)
Epiphytic lichens can exert some negative actions on trees, since they penetrate to different degrees into several tissues of the phytophore. Evernia prunastri (L.) Ach. hyphae progress into xylem vessels of Fagus sylvatica, Quercus pyrenaica and Betula alba. This is on the basis of a mechanism through which Lichens inject metabolic inhibitors in the xylem vessels, and, after their translocation in the xylem sap, they reach different organs of the phytophore and produce defoliation. In this report, we have noted that usnic acid is more impermeant than atranorin through the chloroplast membrane of Quercus rotundifolia leaves. On the other hand, we have also noted the degradation of chlorophyll in response to Lichen substances.
Keywords: chlorophyll degradation; Evernia prunastri; lichen phenols; Quercus rotundifolia

Chlorophyll degradation effected by lichen substances - Bouaid, K.; Vicente, C. (ANNALES BOTANICI FENNICI, 1998)
Epiphytic lichens can exert some negative actions on trees, since they penetrate to different degrees into several tissues of the phytophore. Evernia prunastri (L.) Ach. hyphae progress into xylem vessels of Fagus sylvatica, Quercus pyrenaica and Betula alba. This is on the basis of a mechanism through which Lichens inject metabolic inhibitors in the xylem vessels, and, after their translocation in the xylem sap, they reach different organs of the phytophore and produce defoliation. In this report, we have noted that usnic acid is more impermeant than atranorin through the chloroplast membrane of Quercus rotundifolia leaves. On the other hand, we have also noted the degradation of chlorophyll in response to Lichen substances.
The following values have no corresponding Zotero field: pub-location: UNIV HELSINKI P O BOX 17 (P. RAUTATIEKATU 13), FIN-00014 HELSINKI, FINLAND publisher: FINNISH ZOOLOGICAL BOTANICAL PUBLISHING BOARD
Keywords: chlorophyll degradation; Evernia prunastri; lichen phenols; Quercus rotundifolia

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

CONTRIBUCIÓN AL ESTUDIO DE LA SECA DE LA ENCINA (Quercus rotundifolia Lam.) EN EL NOROESTE DE LA PROVINCIA DE ALBACETE - MONREAL MONTOYA, J A; GALLETERO BLAZQUEZ, A. CHUMILLAS FERNÁNDEZ, R; SALVADOR ANDRÉS, D (II Congreso Forestal Español, 1997)
This paper is a study of the different hypotheses presented up to the present to try and explain reasons for the withering / drying up of oak trees, a serious problem which is taking a high to11 in our oak forests. Initial and follow-up studies have been carried out in N.W. Albacete on the different conditions that we have then used as parameters. Next, relationships have been established among these parameters and, finally, various conclusions have been reached.
Keywords: Albacete; Oak decline; Quercus rotundifolia

El ciclo de biomasa en bosques de frondosas del sur de extremadura. variabilidad espacial del desfronde - TORRES, E; CUEVAS, S; VÁZQUEZ, F Ma; SUÁREZ, Ma A (II Congreso Forestal Español, 1997)
The knowledge of the biomass and nutrients cycle is very important for a suitable forest management. In this paper, four broadleaved species litterfall, during november 1996, is studied in Extremadura (Spain): Castanea sativa Miller, Quercus pyrenaica Willd, Q. rotundifolia Lam and Q. suber L. Litterfall is compared in sorne forests with different maturity. Also, orientation, position and individual tree factors influence is analysed
Keywords: Castanea sativa; Extremadura; litterfall; Quercus pyrenaica; Quercus rotundifolia; Quercus suber

Fenofases florales en quercus rotundifolia lam. - Vázquez, F M (II Congreso Forestal Español, 1997)
In this work the floral stages are introduced that it is happened in the masculine and feminine flowering of the holm-oak (Quercus rotundifolia Lam.). In each described stages they incorporate data on the floral morphology: state of development that it reach the catkins, the floral group and the tlowers. Also data of the receptive state in the are inserted feminine tlowers and ripening and viability grade of the grain of ponen and ovule. Finally is represented in a graphic each one of the described stage. K.W.:
Keywords: flowering; holm-oak; Ovule; pollen; Quercus rotundifolia; reproduction; Stages

Dynamics of bioelements during leaf decomposition in three forest ecosystems of semiarid climate in the Duero Basin - Hernández, M I; Santa Regina, I; Gallardo, J F (Arid Soil Research and Rehabilitation, 1995)
The dynamics of bioelements lost during leaf litter decomposition were experimentally determined in three forest ecosystems located in a semiarid zone of the Duero Basin, Province of Zamora, Spain, during 2 years. The three ecosystems were a climax Quercus rotundifolia (evergreen oak) woodland, a paraclimax Pinus pinea (stone pine) forest, and a disclimax P. pinaster (maritime pine) forest. The total content of bioelements found in the litter was low in relation to other forest ecosystems: 27, 14, and 8 kg N ha?1 in Q. pyrenaica, P. pinea, and P. pinaster, respectively; 17, 10, and 9 kg Ca ha?1, respectively; about 2 kg P ha?1, 4 kg K ha?1, and 5 kg Mg ha?1 in the three forests. The Q. rotundifolia woodland potentially returns a greater amount of N and Ca than both Pinus forests. An in situ litter bag method was used for the determination of dynamics of the decomposing leaves. A progressive loss of C, P, and Mg in the decomposing oak leaves and pine needles, and a sharp loss of K were observed; by comparison, a tendency to maintain N and Ca was seen. Pinus pinaster forest had the lowest annual N and P return.
doi: 10.1080/15324989509385911
Keywords: biogeochemical cycles; litter decomposition; pine forests; Quercus rotundifolia; semiarid forests

Seasonal water potential changes and proline accumulation in Mediterranean shrubland species - Lansac, A R; ZABALLOS, J P; Martin, A (Plant Ecology, 1994)
We studied the water relations of 6 shrub and 3 tree species typical of the mediterranean climate region of central Spain to identify differential responses to water stress between and within species, and to determine if free proline concentration in leaves could be used as a water stress indicator. Predawn and midday water potentials (ffdw) on a seasonal basis, relative water content (RWC), leaf mass per area, foliar nitrogen and free proline concentrations were measured. The lowest water potentials were observed at the end of the summer, with recovery to higher water potentials in the fall and winter seasons. Species differed regarding the annual qdw fluctuation. Thymus zygis, Halimium viscosum, Genista hirsuta and Juniperus oxycedrus exhibited the most negative midday and predawn ~ w (both less than -6 MPa) with a large magnitude of response to changing conditions in soil moisture of the upper horizon of the soil. Lavandula pedunculata and Cistus ladanifer showed a moderate response. Quercus rotundifolia, Quercus faginea and Retama sphaerocarpa showed a modest response. The ~ w of different size individuals of Quercus rotundifolia and Cistus ladanifer were compared. The annual fflw fluctuation was greater in small individuals as compared to large individuals. In every species, there was an increase in proline concentration of bulk leaf tissues when predawn kVw dropped below -5 MPa. Small plants of Cistus ladanifer reached lower water potentials and also higher concentration of proline than bigger plants. Proline could possibly be used as a drought stress indicator in every species except Q. rotundifolia. It is suggested that in addition to water stress avoidance due to deep root systems, some mechanisms of water stress tolerance may operate among shrub and tree species of central Spain.
Keywords: Cistus ladanifer; Genista hirsuta; Halimium viscosum; Juniperus oxycedrus; Lavandula pedunculata; Leaf mass per area; nitrogen; Proline; Quercus faginea; Quercus rotundifolia; Relative water content; retama sphaerocarpa; Thymus zygis; water potential

DRY-MATTER INTAKE PER MOUTHFUL BY GRAZING DAIRY GOATS - PEINADOLUCENA, E; SANCHEZRODRIGUEZ, M; GOMEZCASTRO, A G; MATAMORENO, C; GALLEGOBARRERA, J A (SMALL RUMINANT RESEARCH, 1992)
Mouthful grass intake varied widely from season to season, with minimal values in winter (0.09 g DM) that increased to 0.51 g DM in Spring and decreased in Summer (0.21 g DM). Mouthful intake for shrubby species ranged between lowest for Cistus salvifolius (0.16-0.33 g DM) to C. ladanifer (0.95-3.57 g DM), followed by C. albidus (0.33-1.46 g DM). Quercus rotundifolia was the most frequently ingested arboreal species throughout the year, although the maximum DM content per mouthful (1.58 g) was for Olea europaea. These results show that the greatest weight per mouthful of grass was in spring. The largest amount of DM on a year-round basis was provided by the shrub (C. ladanifer, and the tree O. europaea. Differences in DM intake per mouthful for each species suggest that studies of comparative palatability based on grazing time or number of mouthfuls may lead to errors when estimating actual DM intake for different species studied. Such estimates should be corrected in the light of relative weight per mouthful for each food species.
APS
Keywords: Grazing; Olea europaea; Quercus rotundifolia

Mediterranean evergreen oak diversity: morphological and chemical variation of acorns - Afzal-Rafii, Zara; Dodd, Richard S.; Pelleau, Yvonne (Canadian Journal of Botany, 1992)
Acorns of mediterranean evergreen oak were collected from eight ecogeographically contrasting localities in Italy and Spain. Biometrical analysis of acorns and their cupules showed much greater variation among Spanish populations, encompassing the variation in Italy. The Spanish population at El Pardo, considered the type locality for Quercus rotundifolia, separated from all others. Multivariate analyses of the chemical data indicated, on the one hand, separation of Spain from Italy, and on the other hand, a separation of interior Spanish populations from coastal populations. The importance of lipid composition in the former separation may reflect genetic differentiation between these two origins. Coastal populations were closer to Italian and we suggest were a zone of introgression and hybridization between Quercus ilex and Q. rotundifolia and probably also Quercus coccifera at Bonete Albacete
doi: 10.1139/b92-184doi: 10.1139/b92-184The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: biometry; chemistry; diversity; ecogeography; Quercus ilex; Quercus rotundifolia

ABUNDANCE AND FOOD-SEARCHING INTENSITY OF WOOD MICE (APODEMUS-SYLVATICUS) IN FRAGMENTED FORESTS - Tellería, J L; Santos, T; ALCANTARA, M (JOURNAL OF MAMMALOGY, 1991)
Abundance, food-searching intensity, physiological status, and population attributes of wood mice (Apodemus sylvaticus) were studied in forest islands of central Spain. Seventeen isolated woodlots (Quercus rotundifolia) ranging from 0.1 to 280 ha were studied. The results show high densities of mice and high rates of predation on acorns in the smaller forests.
Keywords: acorns predation; Apodemus sylvaticus; forest islands; Quercus rotundifolia; Spain; wood mice

Chemosystematic differentiation of Quercus ilex and Q. rotundifolia based on acorn steroids - Rafii, Zara A; Zavarin, Eugene; Pelleau, Y (Biochemical Systematics and Ecology, 1991)
Acorns from 34 individual Quercus ilex and Q. rotundifolia trees from 11 locations in Italy and Spain were sampled and analysed for composition of steroids. β-Sitosterol was most abundant in all populations. Concentrations of both stigmasterol and Δ5-avenasterol varied between individual populations in both countries. Δ7-Stigmastenol was not detected in Italian populations and brassicasterol, while absent from the Spanish specimens, was present in the Italian Uccellino population. Principal component analysis showed complete separation of Q. rotundifolia (Spain) and Q. ilex (Italy).
Keywords: acorns; chemosystematics; evergreen oak; fatty acids; Quercus ilex; Quercus rotundifolia; steroids

Pattern detection in plant populations through the analysis of plant-to-all-plants distances - Galiano, E F (Plant Ecology, 1982)
A method of sampling and analysis is proposed to detect pattern parameters in plant populations from two-dimensional data. The use of aerial photographs to find the coordinates of trees and the measurements of plant-to-all-plants distances yields conditioned probability spectra which can be interpreted in terms of pattern parameters. Two artificial populations and a set of real data have been analysed to test the accuracy of the method.
Keywords: nearest neighbour; pattern detection; Quercus rotundifolia

O passado, o presente eo futuro dos montados. Estudo económico agrícola no Distrito de Beja - Carvalho, E. F. N. (1870)
NA
Keywords: Beja; montado; Quercus rotundifolia; Quercus suber

Os montados em Portugal - Luz, C S (1866)
NA
Keywords: montado; Quercus rotundifolia; Quercus suber